The complete mitogenome of Hemiculter leucisculus (Basilewsky, 1855) in Hainan Island and its phylogenetic status - Congqiang Luo; Peng Chen; Jibin Zhu; Zemin Ma (Mitochondrial DNA. Part B. Resources, 2022)
The sharpbelly, Hemiculter leucisculus (Basilewsky, 1855) is a small cyprinid fish that has a wide distribution in East Asia. In this study, we characterized the complete mitochondrial genome of H. leucisculus in Hainan Island using Illumina MiSeq platform. The mitogenome contained 16,621 bp with AT content of 56.2%. The mitogenome of H. leucisculus comprised 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and one control region (D-loop). Phylogenetic analyses indicated that H. leucisculus in the Hainan Island formed independent lineage and the species of H. leucisculus might be a paraphyletic taxon.